Six Floor Origin A Media JIT Packaging And Storage Platform - Pereira, Filipe Fernandez (2024)
In an era where streaming has become essential for news, entertainment and social media, the demand for streaming platforms is increasing. These platforms must implement efficient, scalable and resilient storage solutions and ensure fast, reliable content delivery to the client. This thesis, completed in collaboration with Six Floor Solutions, focuses on developing and implementing a streaming platform that integrates resilient storage algorithms, a service oriented architecture and HTTP streaming protocols. The designed platform ensures secure content storage and efficient streaming delivery. Additionally, when integrated with other proprietary software developed by the company, it introduces a fully automated, AI-powered ad replacement and insertion feature. The development of this project involves complex error correction algorithms, full-stack programming and media content manipulation, implemented in different programming languages such as Python, Java, SQL and Bash. The resulting platform supports four streaming types, features a caching system to reduce delivery times, and is compatible with most media players. It is completely scalable and configurable, adapting to the number of disks on each server, and fully server-agnostic, facilitating its installation in other servers. The platform has been extensively tested with different media content with varying resolutions, demonstrating an effective delivery performance. A Proof of Concept was also created to validate the implemented features through the developed controller web server. Although some modifications can be done to improve the system’s security and resilience, the developed platform is capable of efficiently handling multiple channels and a high volume of streaming requests simultaneously.